EFEKTIFITAS SELF CLEANSING MENGUNYAH BUAH SEMANGKA (CITRULLUS LANATUS) DAN BENGKUANG (PACHYRHIZUS EROSUS) TERHADAP DEBRIS INDEKS PADA SISWA/I KELAS IV SD NEGERI 067247 LAU CIH KECAMATAN MEDAN TUNTUNGAN - SIMAREMARE, ASNITA BUNGARIA; Sondang; Rosdiana Tiurlan Simaremare; Jemima Lola Br Ginting Munthe (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Dental and oral health can be affected by a decrease in plaque, a decrease in plaque, and a decrease in the debris index, as well as a decrease in oral hygiene. This study used a descriptive survey method to determine the effectiveness of self-cleansing by chewing semaingkai (Citrullus iatus) and jicama (Paichyrhizus erosus) fruit on the debris index of students at SD Negeri 067247 Laiu Cih, Kecaimaitain Medain Tuntungain.The results of this study showed that the 15 respondents' debris index before chewing semaingkai fruit was 2.2 ml (very low), and after chewing semaingkai fruit it became 8.6 ml (normal). The debris index of 15 respondents before chewing bengkuaing fruit was 2.3 ml (very low), and after chewing bengkuaing fruit it became 6 ml (normal). The debris index of 15 respondents before chewing semaingkai fruit was 1.2 (moderate) and after chewing semaingkai fruit it became 0.3 (good). The debris index of 15 respondents before chewing jicama fruit was 1.34 (fair) and after chewing it increased to 0.47 (good).The conclusion from this study is that self-cleansing occurs, increasing the level of debris index after chewing jicama fruit. According to the respondents, consuming jicama fruit as a self-cleansing method maintains dental and oral hygiene.